Manfaat Manajemen Kepemimpinan Gereja Terhadap Tingkat Kehadiran Pemuda Dalam Ibadah Di Jemaat Pniel Boloy - Julitte Hasna Liance Buek; Lefran Lefran; Alce Mariani Labito (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
Young people are the backbone and future of the church. Young people cannot move actively without someone in charge of youth management and the church, which must motivate young people to develop positively. Therefore, the importance of good management is to organize and support young people to participate more actively in existing services. This study aimed to determine the cause so of the level of youth attendance in worship instability. To find out the benefits of Church leadership management on youth attendance in worship. The research method used is qualitative with the type of case study research to reveal the benefits of church leadership management on youth attendance in worship. The results showed that there were several causes of youth inactivity in worship, such as lack of approach and lack of self-confidence. The management structure has been implemented in the GPIBK Peniel Boloy congregation, such as the division of tasks and implementation to the existing church councils. In the service of the youth community, the members' attendance rate is unstable.